(untitled) (Bioagro, 2020)
The remarkable increase in the productivity of many crops during the twentieth century can be attributed to genetic gains achieved through crop breeding. Cassava has also benefited from technological inputs in the area of breeding. For this reason, the National Institute for Agricultural Research established a cassava-breeding program, through a phenotypic recurrent selection following the vegetative propagation of the crop. With the purpose of evaluating yield stability of 16 varieties of cassava, uniform yield trials were set under two environmental conditions (production areas of Aragua and Cojedes States). The variables evaluated were vegetative growth, and fresh weight and number of roots. The results showed that there was a highly significant genotype by environment interaction for the variables associated with vegetative growth, but the variables associated to production were affected separately by genotype and environment. Seven of the genotypes resulted the best due to their high weight in commercial roots (>16 Mg·ha-1), while the environment of Cojedes State was the best for most variables associated to yield. A feasible explanation for this trend is the impact of the environment on the physiological and nutritional status of the planting material and/or epigenetic effects. The genotypes Inocol 7, Guajira 2, Meven 36-13 and Guajira 6 can be selected for the evaluation of uniform performance tests motivated to superior behavior in terms of commercial roots and top fresh weight.